S02-1: Online Consultation Guidelines ‘Bewust Bewegen’ With Chronic Diseases (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: The primary purpose of the online consultation guidelines is to support health care professionals in providing a very brief and evidence based advice on physical activity to patients with the most common chronic diseases. Hence, making it easier for healthcare professionals to integrate physical activity promotion into regular care.Project. Development: The consultation guidelines “Bewust Bewegen” were developed by the Knowledge Centre for Sports and Physical Activity in the Netherlands, in collaboration with Moving Medicine, an initiative from the Faculty of Sport and Exercise Medicine (United Kingdom). The guidelines are developed to meet the needs of healthcare professionals with limited time for lifestyle/physical activity counselling.The developmental process was guided by scientific evidence, and input and feedback from scientific as well as healthcare professionals, including doctors, physical therapists, nurses etc. was incorporated. “Bewust Bewegen” was launched in March 2024.Implementation: “Bewust Bewegen” is a free online tool. The tool provides structured consultation guides for very brief (1 minute) and brief (5 minute) conversations and in-depth background information about mechanism, advice, contra-indications, and referral options.Evaluation: Both qualitative and quantitative data is collected. For example, all users receive an evaluation form three months after registration to gather insights on their experiences, such as information for which goals they use the guidelines, how they rate the guidelines, and which information is missed. From launch to January 2025, 555 professionals have used the online consultation guidelines. In total 36 professionals have completed the evaluation form. The overall score for the online consultations is 7.8 (scale 1–10), and is mostly used in consultation or in preparation for the consultation.Dissemination: The dissemination primarily occurs through healthcare professional associations, both online and offline. In addition, the guidelines are promoted via newsletters, articles, conferences, and podcasts.Conclusion: “Bewust Bewegen” aims to help healthcare professionals in the Netherlands to conduct a ‘very brief advice’ consultation about physical activity for people with various chronic conditions and provides information about the specific advice, referral options, and contraindications. Considering the results from the evaluation so far, it seems likely that the concept of very brief advice appeals to healthcare professionals.